Hebrews - Heen, Erik M.; Krey, D. W. Philip. 1950- (Downers Grove, Illinois : InterVarsity Press, 2005)
"Distinctive in form, content and style, the epistle to the Hebrews offers a profound high Christology and makes an awe-inspiring contribution to our understanding of Jesus as our High Priest. The earliest extant commentary on the letter comes to us in thirty-four homilies from John Chrysostom. These homilies serve to anchor the excerpts chosen by the editors of this volume because of their unique place in the history of interpretation. In addition to being the first comprehensive commentary on the letter, they deeply influenced subsequent interpretation in both the East and the West, and their rhetorical eloquence has long been acknowledged."--BOOK JACKET.
Includes bibliographical references (p. 267-280) and index.
Keywords: N.T. Hebrews -- commentaries